TB and SIV Coinfection; a Model for Evaluating Vaccine Strategies against TB Reactivation in Asian Origin Cynomolgus Macaques: A Pilot Study Using BCG Vaccination - Andrew D. White; Laura Sibley; Jennie Gullick; Charlotte Sarfas; Simon Clark; Zahra Fagrouch; Ernst Verschoor; Francisco J. Salguero; Mike Dennis; Sally Sharpe (Vaccines, 2021)
This pilot study aimed to determine the utility of a cynomolgus macaque model of coinfection with simian immunodeficiency virus (SIV) for the assessment of vaccines designed to prevent reactivation of TB. Following infection caused by aerosol exposure to an ultralow dose of Mycobacterium tuberculosis (M. tb), data trends indicated that subsequent coinfection with SIVmac32H perturbed control of M. tb infection as evidenced by the increased occurrence of progressive disease in this group, higher levels of pathology and increased frequency of progressive tuberculous granulomas in the lung. BCG vaccination led to improved control of TB-induced disease and lower viral load in comparison to unvaccinated coinfected animals. The M. tb-specific IFNγ response after exposure to M. tb, previously shown to be associated with bacterial burden, was lower in the BCG-vaccinated group than in the unvaccinated groups. Levels of CD4+ and CD8+ T cells decreased in coinfected animals, with counts recovering more quickly in the BCG-vaccinated group. This pilot study provides proof of concept to support the use of the model for evaluation of interventions against reactivated/exacerbated TB caused by human immunodeficiency virus (HIV) infection.